2015
DOI: 10.1371/journal.pone.0126762
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Molecular Portrait of Triple Negative Breast Tumors in an Understudied Population through Omics Analysis of Formalin-Fixed and Paraffin-Embedded Tissues

Abstract: Triple negative breast cancer (TNBC), defined by the lack of expression of the estrogen receptor, progesterone receptor and human epidermal receptor 2, is an aggressive form of breast cancer that is more prevalent in certain populations, in particular in low- and middle-income regions. The detailed molecular features of TNBC in these regions remain unexplored as samples are mostly accessible as formalin-fixed paraffin embedded (FFPE) archived tissues, a challenging material for advanced genomic and transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
4
14
1
Order By: Relevance
“…Pathway analysis of potentially functional mutations across all genes showed enrichment of signal transduction pathways including EGFR, PDGF and IGF1R, and mutational signatures showed a large contribution of DNA repair defects to the mutation load. These overall results on TN cases fit with our previous analyses of another series of TN cases from Mexico where transcriptomics analyses showed an overexpression of growth-promoting signals (including EGFR, PDGFR and PIK3CA), a repression of cell cycle control pathways (TP53, RB1) and a deregulation of DNA-repair pathways [46].…”
Section: Discussionsupporting
confidence: 90%
“…Pathway analysis of potentially functional mutations across all genes showed enrichment of signal transduction pathways including EGFR, PDGF and IGF1R, and mutational signatures showed a large contribution of DNA repair defects to the mutation load. These overall results on TN cases fit with our previous analyses of another series of TN cases from Mexico where transcriptomics analyses showed an overexpression of growth-promoting signals (including EGFR, PDGFR and PIK3CA), a repression of cell cycle control pathways (TP53, RB1) and a deregulation of DNA-repair pathways [46].…”
Section: Discussionsupporting
confidence: 90%
“…In Mexico, Vaca-Paniagua et al (41) reported TP53 and RB1 as the most frequently mutated genes in TNBC by complete exome sequencing. Differences in the results found in our work with respect to RB1 could be attributed to the design of the study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that miRNAs play important roles in the initiation, development, metastasis and resistance to treatment of TNBC [31,32]. Tumor suppressive miRNAs mediate the degradation or post-transcriptional inhibition of transcripts encoding oncogenes and can target ZEB1/2, HMGB2, Bcl2 and HIF-1α, which contribute to the increased proliferation, invasion, and EMT and reduce the apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%